Efektifitas Pemberian Pupuk Organik Kandang Kambing dan Pupuk Organik Cair Urin Kambing Terhadap Pertumbuhan dan Produksi Tanaman Bayam Merah (Althernanthera amoena Voss): Effectiveness of Goat Manure and Goat Urine Fertilizer to Growth and Production of Red Spinach (Althernanthera amoena Voss) - Meci Yuniastuti Rahma; Fitri Damayanti (Politeknik Negeri Lampung, 2021)
Red spinach plants are used as a food source of protein, especially for developing countries, so that the growth and yield of red spinach increases, it is necessary to add additional nutrient input from organic fertilizers such as goat manure and goat urine. This study aims to determine the effectiveness of goat manure organic fertilizer and the effect of the interaction of goat urine liquid fertilizer on red spinach plants. The research was carried out from March 2018 to April 2018 in Sambirejo Village, Jalan Sabar Jaya, Banyuasin 1 District, South Sumatra. This study was arranged using a factorial randomized block design (RAKF) with three replications. The factors used were goat manure organic fertilizer consisting of three levels, namely K0, K1, K2 and goat urine liquid organic fertilizer consisting of five levels, namely U0, U1, U2, U3, U4. The parameters observed consisted of number of leaves (strands), root length (cm), plant height (cm), plant dry weight (g), plant fresh weight (g). The application of organic fertilizer only affects goat manure but does not affect the production of red spinach plants, it’s just that in the K2U2 treatment (10 shows the best production on the number of leaves and weight of wet bark. Key words : Goat Manure Fertilizer, Goat Urine Fertilizer, Red Spinach